Digital learning in Sciences education: A literature review - Momani, Manal Abdul Karim Al; Alharahasheh, Kawther Aboud; Alqudah, Mohammad (Cogent education, 2023)
This study looked at 8760 Web of scientific research publications about digital learning in scientific education. The researchers discovered seven clusters with 59 affiliations, 36 keywords, and 135 authors from 28 countries using bibliometric and text analysis approaches. The study provides useful insights into the present status of digital learning literature, providing recommendations to scholars and educators in this sector. The research highlighted the use of technology to improve scientific teaching by evaluating the data. The findings have consequences for academics, educators, and policymakers, allowing them to better understand current research and propose prospective topics for future study in digital learning in scientific education.